Analysis of clinical information and reverse transcriptase-polymerase chain reaction for early diagnosis of enteroviral meningitis - Dahee Jin; Tae Hoon Heo; Jung Hye Byeon; Gun-Ha Kim; Mi Kyung Kim; So-Hee Eun; Baik-Lin Eun (Korean Journal of Pediatrics, 2015)
PurposeMeningitis is among the most common infections affecting the central nervous system. It can be difficult to determine the exact pathogen responsible for the infection and patients are often treated with empiric antibiotics. This study was conducted to identify the most common clinical characteristics of enteroviral meningitis in children and evaluate the diagnostic efficacy of reverse transcriptase-polymerase chain reaction (RT-PCR) for early detection of an enterovirus.MethodsWe analyzed the medical records of children admitted to Korea University Medical Center and diagnosed with meningitis on the basis of cerebrospinal fluid (CSF) analysis and RT-PCR from CSF and other samples from January 2010 to August 2013.ResultsA total of 333 patients were enrolled and classified into four groups based on diagnosis: enteroviral meningitis (n=110), bacterial meningitis (n=23), other viral meningitis (n=36), and unknown etiology (n=164). Patients with bacterial meningitis were younger than those in the other groups (P<0.001). Pleocytosis in CSF was similar across all groups. Of patients in the enteroviral meningitis group, 92.7% were diagnosed based on RT-PCR findings. Mean length of hospital stay for patients with enteroviral meningitis was 6.08 days, which was significantly shorter than that for patients with meningitis of bacterial etiology (19.73 days, P<0.001).ConclusionDiagnosis of enteroviral meningitis before viral culture results are available is possible using RT-PCR. Accurate diagnosis reduces the length of hospital stay and helps to avoid unnecessary empiric antibiotic treatment.